Exploring team dynamics and performance in extended space missions using agent-based modeling - Iser Pena; Hao Chen (PLoS ONE, 2025)
As humanity prepares for crewed missions to Mars, these will be among the most extended and isolated journeys, presenting challenges in team performance and dynamics. The extreme isolation, prolonged confinement, and necessity for autonomous decision-making without Earth support demand a comprehensive understanding of crew interactions and psychological resilience. This study addresses this need by integrating psychological theories with agent-based modeling (ABM) to simulate the impact of team composition over a 500-day Mars mission. Utilizing the Five-Factor Model (FFM) of personality traits, agents varying in openness, conscientiousness, neuroticism, extraversion, and agreeableness were modeled to form both heterogeneous and homogeneous teams. To capture functional as well as psychological diversity, the framework also incorporates variation in skills and roles, enabling a 2 × 2 factorial design that disentangles the effects of personality heterogeneity, role heterogeneity, and their interaction. Our results suggest that team composition influences stress, health, performance, and cohesion, with personality variation and role specialization contributing distinctly. When combined, these factors appear to generate interaction effects relevant for crew selection, training, and preparation. These findings underscore the importance of jointly considering personality and functional diversity when developing strategies to support resilience and effectiveness in long-duration spaceflight.